Appraising the impact of COVID-19 on trading volume of selected vessel types in sub-Saharan Africa - Olabisi Michael Olapoju (Journal of Shipping and Trade, 2023)
Abstract The emergence and diffusion of coronavirus (COVID-19) have brought a lot of impacts on various spheres of human endeavours including maritime trading. This paper explores the effect of the lockdown on maritime port calls for selected vessels in the sub-Saharan African (SSA) regions (East, Middle, South, and West Africa). The study utilizes port calls data of the maritime profile of the global economies obtained from the United Nations Conference on Trade and Development Statistics between 2018 and 2021. Data include port calls for liquid bulk carrier, liquefied petroleum gas, dry bulk carrier, dry break bulk carrier, roll-on-roll-off, and container carrier. The analysis of data involves the use of exploratory technique to reveal dimensions of performance by various carriers across the regions. The results picture the kind of response of port calls in all the regions akin to the response from other regions of the world. However, the study observes that though responses to COVID-19 lockdown across the globe were similar, SSA regions were slow in recovering from the decline in port calls when compared to the developed and some rapidly developing economies of the world due to the region’s lack of economic resilience. Thus, since ports have been identified as vulnerable to economic, social, institutional, and environmental shocks, and to dynamic and highly unpredictable demand for port services, policymakers of various nationals in the SSA may need to examine the patterns of performance of vessels in the regions to manage trade flows more effectively as a way of responding to future dynamics in maritime trade in the region.